Integrating Dulmuluk Theater into Character Education: A Cultural Approach to Social Transformation in Schools - Nugroho Notosutanto Arhon Dhony; Wadiyo Wadiyo; Nur Sahid; Agus Cahyono (AL-ISHLAH: Jurnal Pendidikan, 2025)
This study examines how Dulmuluk theater—a traditional performing art from Palembang, Indonesia—can be integrated into formal education as a medium for character development and social transformation. While recognized as cultural heritage, its pedagogical use in schools remains underexplored. A qualitative hermeneutic phenomenological approach was employed to understand the lived experiences of educators and students involved in Dulmuluk-based learning. Data were collected through classroom observations, semi-structured interviews with 3 teachers and 6 students, documentation review, and audiovisual materials. Thematic analysis was used to interpret the data. Findings revealed that Dulmuluk theater effectively conveys moral values such as honesty, discipline, environmental awareness, respect for parents, social solidarity, and responsibility. These values are internalized through a three-stage process: understanding (exploration of scripts and character analysis), application (performance-based learning and collaboration), and habituation (reflection and behavior reinforcement). Students demonstrated improved moral reasoning, social interaction, and empathy through their engagement with the theater. The integration of Dulmuluk into character education aligns with constructivist and socio-cultural learning theories by fostering experiential, affective, and culturally relevant learning. It serves as a powerful tool for reinforcing local values, enhancing emotional literacy, and supporting inclusive, democratic learning environments. The study recommends formal curriculum integration and teacher training to support this approach.